Exploration Physics Concepts In Local Wisdom Mappere Bone South Sulawesi as A Source of Physics Learning: An Analytical Study - Mohd Zaidi Bin Amiruddin; Suliyanah Suliyanah (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
The development of physics continues to grow. This is because physics is one of the sciences that study the behaviour of nature with various forms of applicable symptoms. This study aims to explore the concept of physics in Mappere as a source of learning physics, provide information related to one of the local wisdom in Bone, and attempt to preserve Mappere through writing and learning resources analytical study approach. Data collection is used in literature studies, observations, and interviews. Data search is done by finding as many sources of information as possible through scientific studies, journal articles, or reliable sources. The results obtained from this study are that there is a physics concept in the Mappere which can be used as a contextual learning resource for students. In addition, it turns out that local wisdom can be used as a contextual learning resource with their respective characteristics. Thus, it can be concluded that local wisdom can be an alternative in learning in schools in order to provide concrete examples for students to better understand learning, especially in learning physics. It is hoped that research on local wisdom will continue to be developed so that it can provide a real example in education while at the same time preserving the ancestral culture that is more useful.